Understanding the contents of a lesson plan and the stages of a lesson (Journal of Science-Innovative Research in Uzbekistan, 2024)
Aims are what teachers (and learners) want to achieve in a lesson or a course. Activity in a class is planned in order to achieve these aims.A lesson aim could be for the learners to demonstrate that they understand the form or use of the passive better, or to have practised intensive reading. A course aim could be to improve the report writing skills of a group of business students.